THE DURATION OF INTERNET USE ON AUDIENCE SATISFACTION READING ONLINE MEDIA - La Taya, La Taya; Genggong, Marsia Sumule; Tawai, Adrian (Laboratorium Ilmu Komunikasi Fisip UHO, 2024)
The development of online-based mass media is now increasingly massive in Indonesia, including in Southeast Sulawesi. Initially, audiences control conventional media; with online media, audiences can choose media for reference according to their needs. This study aims to determine the satisfaction of online media audiences in Southeast Sulawesi, which includes joy in seeking information, satisfaction with personal identity, satisfaction with integration and social interaction, and satisfaction with diversion or entertainment. Researchers conducted this study in Kendari City and determined a sample of 98 people using the Slovin formula. The researchers employed axial sampling. The analysis of this research data is descriptive statistics, which describes events and the behavior of certain things presented in tables and diagrams. The results showed that the satisfaction of online media audiences in Southeast Sulawesi was highest on several dimensions, namely the pleasure of searching for information in the region, especially local news, building trust, and seeking the information as a basis for decision-making and seeking information to strengthen relationships with others and collect entertaining details. The results of this research will enable online media to deliver trustworthy news or articles that cater to the public's needs, allowing readers to acquire knowledge.